PENGARUH PELATIHAN, FASILITAS KERJA, DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BPJS KETENAGAKERJAAN BOGOR CILEUNGSI - Mia Eka Wulandari (2021)
This study is a quantitative that aims to determine the effect of training, work facilities and motivation on employee performance. The population in this study were all employees who worked at BPJS Ketenagakerjaan Bogor Cileungsi and used a saturated sample or census as a data collection method to 39 respondents. The data analysis technique used is descriptive analysis, and inferential analysis with a significant level of 5% (0.05) used Partial Least Square (PLS) test equipment with smrtPLS 3.0 software. The results of this study indicate that: (1) partially training has a positive and significant effect on employee performance with a value of tcount 2.403 > ttable 1.689 (2) partially work facilities have a positive and significant effect on employee performance with a value of tcount 3.325 > ttable 1.689 (3) Partially, motivation has a positive and significant effect on employee performance with a value of tcount 4.316 > ttable 1.689. And has an R Square value of 0.879 or 87.9%.